The employment practices in multinationals in Belgium - Pulignano, Valeria; Dekocker, Vickie (Leuven, 2014)
"The study explores the impact of key aspects of MNCs' structure and organisation on HRM and employment practices. Key aspects include broad structural factors such as country of origin, sector and size on the one hand, and internal organisational factors such as the degree of international product diversification, the extent of international integration of operations and international structures, on the other hand."